Profiles in Christian courage : extraordinary inspiration for everyday life - Walters, Kerry S. (Lanham, Maryland : Rowman & Littlefield, 2014)
The author explores the meaning and scope of Christian courage, offers tips on how to cultivate it in daily life, and offers profiles of Christians who have exemplified it in their own lives. The portraits are of modern women and men, some famous and some lesser known, from all parts of the globe, who have displayed physical, moral, or spiritual courage.
Preface -- Who would true valor see -- Part I: Physical courage -- Michael Lapsley -- The Fraternal Martyrs of Burundi -- Dorothy Stang -- Alexander Men -- The Tibhirine Monks -- Mychal Judge -- Part II: Moral Courage -- Ruth Manorama -- Shahbaz Bhatti -- The Nickel Mines Amish -- Li Ying -- Emil Kapaun -- Clarence Jordan -- Part III: Spiritual Courage -- Dianna Ortiz -- Walter Ciszek -- Thea Bowman -- C.S. Lewis -- Henri Nouwen -- Mother Teresa -- Everyday courage for everyday Christians -- Notes -- Index.
Includes bibliographical references and index.
Keywords: Christian biography; Courage